2006
DOI: 10.1007/s00709-006-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity dependence of excitable biological and physicochemical media

Abstract: Neuronal tissue and especially the central nervous system (CNS) is an excitable medium. Self-organisation, pattern formation, and propagating excitation waves as typical characteristics in excitable media consequently have been found in neuronal tissue. The properties of such phenomena in excitable media do critically depend on the parameters (i.e., electromagnetic fields, temperature, chemical drugs) of the system and on small external forces to which gravity belongs. The spreading depression, a propagating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Our present results complement the previous one obtained using animal neuronal tissues and reveal that plant APs are gravity-sensitive in the same manner as already reported for animal APs 5 6 . We can conclude that APs in root tissues of higher plants and neuronal tissues of animals are gravity-dependent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present results complement the previous one obtained using animal neuronal tissues and reveal that plant APs are gravity-sensitive in the same manner as already reported for animal APs 5 6 . We can conclude that APs in root tissues of higher plants and neuronal tissues of animals are gravity-dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Fast gravity perceiving systems, when the perception of a changing acceleration is rapidly transduced into electrical signals, have been documented from unicellular organisms 4 up to neuronal tissues 5 6 . In plants, numerous studies indicate that cell membranes, membrane proteins and membrane potentials are involved in the perception of gravity 7 8 9 .…”
mentioning
confidence: 99%
“…The velocity of SD waves of retinal eyecups from chickens was slower under microgravity and faster under hypergravity (parabolic flights and centrifuges). 68 – 71 However, the SD waves were faster during a sounding rocket mission (TEXUS). 68 The authors speculated that a possible adaptation effect from the launch could have been the reason for this disagreement.…”
Section: Electrophysiological Experiments In Microgravitymentioning
confidence: 99%
“… 68 – 71 However, the SD waves were faster during a sounding rocket mission (TEXUS). 68 The authors speculated that a possible adaptation effect from the launch could have been the reason for this disagreement.…”
Section: Electrophysiological Experiments In Microgravitymentioning
confidence: 99%
“…A physical parameter always present on Earth is gravity (1g), but micro-g or macro-g can significantly influence neuronal tissue as has been tested using the retinal SD (Wiedemann et al 2005;Hanke et al 2006) in parabolic flights and sounding rocket missions as well as in a laboratory centrifuge. It has been shown that the waves significantly slow down under micro-g and accelerate at higher g-values.…”
Section: Resultsmentioning
confidence: 99%